Seminaire Bourbaki lectures - Seminaire Bourbaki, volume 1997/98, exposes 835-849; Seminaire Bourbaki (Paris Societe Mathematique de France, 1998)
As in the preceding volumes of this seminar, one finds here fifteen survey lectures on topics of current interest: one lecture on differential Galois theory, one on Riemannian geometry, one on symplectic geometry, one on Hecke algebras, one on quasi-cristals, one on the quantization of Poisson manifolds, one on integrable systems and quantum field theory, one on sieve methods, one on loop spaces of compact Lie goups, one on Lie algebras, one on eigenvalues of hermitian matrices, one on quantum cohomology of projective hypersurfaces, one on the fundamental group of curves in algebraic geometry, one on the K-theory of C*-algebras, and finally one on zeta functions.
Keywords: Mathematics